REVIEWING THE DEVELOPMENT PLAN OF TEMON AIRPORT, KULONPROGO DISTRICT IN THE PERSPECTIVE OF INTEGRATIVE SPATIAL PLANNING SYSTEM - Ananda Prima Yurista (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2018)
AbstractThis research is based on the case of airport development in Kulonprogo Regency. The findings in this study are: First, contradictions RTRW Kulonprogo District with RTRWN, RTRW DIY Province, and RZWP3K DIY Province not in accordance with Article 7 paragraph (1) and (2) of Law No. 12 of 2011 on the Establishment of Laws and Regulations. Second, contradictions RTRW Kulonprogo District with RTRWN, RTRW DIY Province, and RZWP3K DIY Province is not in accordance with Article 14 paragraph (2) of Law No. 26 of 2007 on Spatial Planning. Here are some mitigating actions over the contradiction between Article 18 of Regional Regulation of Kulonprogo Regency RTRW: through examination in the Constitutional Court; with the cancellation of Regional Act by the Governor; and, with the amendment the norms of Article 91 Paragraph (2) of the Regional Government Law.IntisariPenelitian ini dilaksanakan terhadap kasus pembangunan bandar udara di Kabupaten Kulonprogo. Temuan dalam penelitian ini diantaranya: Pertama, RTRW Kabupaten Kulonprogo bertentangan dengan RTRWN, RTRW Provinsi DIY, RZWP3K Provinsi DIY, dan Pasal 7 ayat (1) dan (2) UU No. 12 Tahun 2011. Kedua, RTRW Kabupaten Kulonprogo bertentangan dengan Pasal 14 ayat (2) UU No. 26 Tahun 2007. Untuk memitigasi ketentuan dalam Pasal 18 RTRW Kabupaten Kulonprogo, yang harus dilakukan adalah: Pertama, melalui uji material di MA. Kedua, dengan pembatalan Peraturan Daerah oleh Gubernur. Ketiga, dengan perubahan Pasal 91 ayat (2) UU No. 23 Tahun 2014.